Simian Virus 40-Host Cell Interaction During Lytic Infection - Gershey, Edward L. (1979)
Both exponentially growing and serum-arrested subcloned CV-1 cell cultures were infected with simian virus 40 (SV40). By 24 h after infection 96% of the nuclei of these permissive cells contained SV40 T-antigen. Analysis of the average DNA content per cell at various times after infection indicated that by 24 h most of the cells contained amounts of DNA similar to those normally found in G(2) cells. Analysis of cell cycle distributions indicated that a G(2) DNA complement was maintained by over 90% of the cells in the infected populations 24 to 48 h postinfection. Cells continued to synthesize SV40 DNA during the first 50 h after infection, and cytopathic effect was first observed 60 h after inoculation. After infection the number of mitotic cells that could be recovered by selective detachment decreased precipitously and was drastically reduced by 24 h. A study of the kinetics of decline in the number of mitotic cells suggests that this decline is related to an event during the cell cycle at or near the G(1)-S-phase border upon which commencement of SV40 DNA replication apparently depends. It was concluded that after SV40 infection, stationary cells are induced to cycle, and cycling cells complete one round of cellular DNA synthesis but do not divide. Although the infected cells continue to synthesize viral DNA, they do not appear able to reinitiate cellular DNA replication units. These results imply that the abundance of T-antigen (produced independently of cell cycle phase) in the presence of the enzymes required for continued DNA synthesis is not sufficient for reinitiation of cellular DNA synthesis.